The Impact of Public Spending on Unemployment: A Study on the Iraqi Economy for the Period 2004-2021 - حماد، سعد عبدالكريم; شلال، عمار عبدالهادي; العلواني، على كريم عطا الله; الدليمى، فيصل غازي فيصل; اللهيبي، ذاكر هادي عبدالله (مركز رفاد للدراسات والأبحاث, 2023)
الأهداف: تهدف هذه الدراسة إلى بيان أثر الإنفاق العام في معدلات البطالة في الاقتصاد العراقي، من أجل معرفة تأثير الإنفاق العام الذي تقوم به الحكومة هل يؤثر سلبا أم إيجابا على معدلات البطالة. المنهجية تم استخدام نموذج الانحدار الذاتي ذو فترات الإبطاء الموزعة، وذلك اعتمادا على بيانات سلسلة زمنية ربع سنوية للمدة 2004-2021. إذ تم الحصول على البيانات من البنك المركزي العراقي، وتم استخدام برنامج Eviews لإيجاد أثر الإنفاق العام في البطالة. النتائج: أظهرت نتائج التحليل وجود علاقة تكامل مشترك للإنفاق العام في معدل البطالة في العراق خلال مدة البحث، فضلا عن وجود أثر معنوي وعكسي للإنفاق العام في معدل البطالة في الأجل الطويل، فكلما ارتفعت نسبة الإنفاق العام بنسبة (1%) يؤدي ذلك إلى انخفاض معدل البطالة بنسبة (3%). الخلاصة توفر هذه الدراسة معلومات كافية لمتخذي القرار فيما يخص الإنفاق العام بأن زيادة هذا الإنفاق سيؤدي إلى خفض معدلات البطالة، وفي حال تم تخفيض الإنفاق العام فإن معدلات البطالة سترتفع. Objectives: The study Objective is to show the effect of public spending on unemployment rates in the economy of Iraq. Basically, the study aims to determine whether the public spending carried out by the government, affects negatively or positively the unemployment rates. Methods: (ARDL) an autoregressive distributed lag model was used. It is based on quarterly time series data for the period 2004-2021. The data were obtained from the Iraqi Central Bank, and the Eviews program was used to find out the impact of public spending on unemployment. Results: The results showed that there is a co-integration correlation of public spending on the unemployment rates in Iraq during the research period. Results also showed a significant and inverse effect of public spending on the unemployment rates during long period. The increase of the public spending rate by 1% leads to a decrease in the unemployment rate by 3%. Conclusions: This study provides enough information for decision-makers regarding public spending that increasing public spending will decrease the unemployment rates, and vice-versa.
Keywords: الاقتصاد العراقي -- الإنفاق العام -- معدلات البطالة